Mode-coupled Interferometric Multiparameter Measurement Sensor Based on A Dual Microfiber Ring - Du, Jiali; Fan, Jiaqi; Feng, Chao; Guo, Minfei (International Journal of Computer Science and Information Technology, 2026)
A sensor based on dual microfiber ring mode-coupling interference is proposed, which enables simultaneous measurement of temperature and pressure by exploiting mode-coupling interference in bent optical waveguides within dual microfiber rings. The sensor is fabricated by winding microfibers into a dual-ring structure through van der Waals and electrostatic forces. This design not only renders the device compact but also allows the dual-ring structure to realize complex functions within limited space while enhancing sensitivity, making it suitable for integrated applications. Experimental results demonstrate that the sensor achieves a temperature sensitivity of –2.4033 nm/°C and a pressure sensitivity of –4.8863 dBm/kPa. Owing to its distinct response mechanisms to external temperature and pressure variations, the sensor allows simultaneous demodulation of temperature and pressure. Furthermore, the sensor is highly responsive to minute signal changes, making it suitable for real-time monitoring of temperature and stress variations in production lines, thus providing early warning of potential failures and reducing safety risks. With its compact structure and high sensitivity, the proposed microfiber sensor holds great promise for emerging applications in the field of sensing technology.